B-IMPACT project: eco-friendly and non-hazardous coatings for the protection of outdoor bronzes. Issue 1 (November 2020) - Masi, G.; Aufray, M; Balbo, A; Bernardi, E; Bignozzi, MC; Chiavari, C; Esvan, J; Gartner, N; Grassi, V; Josse, C; Kosec, T; Martini, C; et al.
Abstract: Application of protective coatings is the most widely used conservation treatment for outdoor bronzes. Eco-friendly and non-hazardous coatings are currently needed for conservation of outdoor bronze monuments. To fulfil this need, the M-ERA.NET European research project B-IMPACT (Bronze-IMproved non-hazardous PAtina CoaTings) aimed at assessing the protectiveness of innovative coatings for historical and modern bronze monuments exposed outdoors. In this project, two bronze substrates (historical Cu-Sn-Zn-Pb and modern Cu-Si-Mn alloys) were artificially patinated, by acid rain solution using dropping test and by "liver of sulphur" procedure (K2 S aqueous solution) to obtain black patina, respectively. Subsequently, the application of several newly developed protective coatings was carried out and their performance was investigated by preliminary electrochemical tests. In the following steps of the work, the assessment of the best-performing coatings was carried out and their performance was compared to Incralac, one of the most widely used protective coatings in conservation practice. A multi-analytical approach was adopted, considering artificial ageing (carried out in representative conditions, including exposure to rain runoff, stagnant rain and UV radiation) and metal release, as well as visual aspect (so as to include aesthetical impact among the coating selection parameters) and morphological and structural evolution of the coated surfaces due to simulated outdoor exposure. Lastly, also the health impact of selected coatings was assessed by occupational hazard tests. The removability and re-applicability of the best-performing coatings were also assessed. The best alternatives to the conventional Incralac exhibited were: (i) fluoroacrylate blended with methacryloxy-propyl-trimethoxy-silane (FA-MS) applied on patinated Cu-Sn-Zn-Pb bronze and (ii) 3-mercapto-propyl-trimethoxysilane (PropS-SH) applied on patinated Cu-Si-Mn bronze.